Effects of waterborne nitrite on hematological parameters and stress indicators in olive flounders, Paralichthys olivaceus, raised in bio-floc and seawater. (October 2018) - Kim, Jun-Hwan; Kim, Jin-Young; Lim, Lok-Ji; Kim, Su Kyoung; Choi, Hye Sung; Hur, Young Baek
Abstract: Juvenile olive flounders, Paralichthys olivaceus (mean weight 2.69 ± 0.31 g), were raised in bio-floc and seawater for six months, these P. olivaceus (mean weight 280.1 ± 10.5 g, mean length 28.37 ± 2.3 cm) were exposed to different concentrations of waterborne nitrite (0, 25, 50, 100, and 200 mg NO2 − /L) for 7 days. None of the P. olivaceus individuals exposed to bio-floc and seawater containing waterborne nitrite concentrations of 200 mg/L for 7 days survived. Hematological parameters (hemoglobin and hematocrit) were significantly reduced by nitrite exposure. Regarding plasma components, the concentrations of glucose, glutamic oxalate transaminase (GOT), and glutamic pyruvate transaminase (GPT) increased significantly in response to nitrite exposure, whereas cholesterol concentrations significantly decreased. Stress indicators, including concentrations of plasma glucose, cortisol, and liver and gill concentrations of heat shock protein 70 (HSP70) were significantly increased by nitrite exposure. The results of the study indicate that nitrite exposure affected the hematological parameters and stress indicators of P. olivaceus raised in bio-floc and seawater, and these changes were more prominent in the P. olivaceus raised in seawater than those raised in bio-floc. Highlights: Hematological paramaters of P. olivaceus were significantly changed by nitrite. Stress indicators of P. olivaceus raised in bio-floc and seawater were significantly increased by nitrite. Toxic effects on P. olivaceus exposed to nitrite were more prominent in the fish raised in seawater.